Innovations in traditional foods - Galanakis, Charis M. (Woodhead Publishing, 2019)
'Innovations in Traditional Foods' addresses the most relevant topics of traditional foods while placing emphasis on the introduction of innovations and consumer preferences. Certain food categories, such as fruits, grains, nuts, seeds, grains and legumes, vegetables, mushrooms, roots and tubers, table olives and olive oil, wine, fermented foods and beverages, fish, meat, milk and dairy products are addressed. Intended for food scientists, technologists, engineers and chemists working in food science, product developers, SMEs, researchers, academics and professionals, this book provides a reference supporting technological advances, product development improvements and potential positioning in the traditional food market. Key Features: Addresses the most relevant topics of traditional foods while placing emphasis on the introduction of innovations and consumer preferences; Provides a reference supporting technological advances, product development improvements, and potential positioning in the traditional food market; Contains coverage of various food categories, including fruits, grains, nuts, seeds, grains and legumes, vegetables, mushrooms, roots and tubers, table olives and olive oil, wine, fermented foods and beverages, fish, meat, and milk and dairy products. --